2022
DOI: 10.29303/jppipa.v8i3.1197
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of the Socio-scientific Issues Approach with the Investigative Group Learning Model to Improve Students' Critical Thinking Skills on Environmental Change Materials

Abstract: This study aims to determine the effect of the socio-scientific issue approach with the investigative group learning model on the critical thinking skills on environmental change. This study uses a quasi-experimental method with a pretest-posttest control group design. The research population is the students of class X IPA SMAN 1 Batu Sopang, Paser Regency, East Kalimantan, in the academic year 2020/2021. The samples were class X IPA 1 (experimental group) and X IPA 2 (control group) . The test instrument use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 17 publications
0
2
0
2
Order By: Relevance
“…Pendekatan pembelajaran yang digunakan penelitian ini merujuk pada pendekatan pembelajaran yang dicetuskan oleh Zeidler et al, (2005) dimana pendidikan SSI bertujuan guna memicu serta meningkatkan kemajuan intelektual individu dalam etiket dan etika serta pemahaman akan saling ketergantungan antara sains dan masyarakat. Potensi pendekatan SSI terhadap peningkatan komunikasi, kemampuan intelektual, dan sikap sosial (Aisya et al, 2017) (Rosana, 2020) (Jariah & Aminatun 2022).…”
Section: Pendahuluanunclassified
See 1 more Smart Citation
“…Pendekatan pembelajaran yang digunakan penelitian ini merujuk pada pendekatan pembelajaran yang dicetuskan oleh Zeidler et al, (2005) dimana pendidikan SSI bertujuan guna memicu serta meningkatkan kemajuan intelektual individu dalam etiket dan etika serta pemahaman akan saling ketergantungan antara sains dan masyarakat. Potensi pendekatan SSI terhadap peningkatan komunikasi, kemampuan intelektual, dan sikap sosial (Aisya et al, 2017) (Rosana, 2020) (Jariah & Aminatun 2022).…”
Section: Pendahuluanunclassified
“…Kemampuan menemukan fakta yang relevan memiliki indikator dengan nilai rata-rata N-gain 0,59 dan dikategorikan cukup efektif, sedangkan kemampuan menemukan persamaan dan perbedaan suatu objek memiliki indikator dengan nilai rata-rata 0,52 dan dikategorikan cukup efektif. Relevansi sains dalam kehidupan siswa dapat terfasilitasi dengan baik oleh pendekatan SSI (Gutierez, 2015) (Jariah & Aminatun 2022). Implementasi pendekatan SSI memungkinkan siswa mampu mengeksplorasi konten sains dan memfasilitasi permasalahan dunia nyata kemasyarakatan (Rostikawati, 2016).…”
Section: Pendahuluanunclassified
“…Research by Silva et al,( 2023), states that the GI model influences students' critical thinking skills and creative thinking skills. Jariah & Aminatun (2022), research findings thatthe socio-scientific approach to issues with the GI learning model proved to be more effective in improving students' critical thinking skills than conventional learning models. The research conducted is different from other studies, in this study using investigative and thinking learning strategies, namely the GITTW strategy where the TTW syntax is integrated into the GI syntax.…”
Section: Introductionmentioning
confidence: 98%
“…Previous research has found that implementing the problem-based learning model can increase student participation in school, with various subjects and learning materials (Dian et al, 2017;Kamala et al, 2022). Furthermore, other research also shows that the use of problem-based learning models can improve scientific literacy (Yani et al, 2020) and critical thinking skills in students (Aufa et al, 2021;Jariah & Aminatun, 2022;Khairunnisa et al, 2022;Rahmadita et al, 2021;Yana et al, 2022). Norman states that there is no strong evidence that learning strategies using PBL produce general improvements.…”
Section: Introductionmentioning
confidence: 99%